Anchorage design for petrochemical facilities (Published by American Society of Civil Engineers, 2013)
This book presents recommendations for the design, fabrication, and installation of anchorages into concrete for petrochemical facilities. Interpreting the intent of building codes as applied to petroleum or chemical installations, this report offers realistic guidance on materials, design details, installation, and repair. It summarizes the state of the practice for the design of cast-in-place anchor rods, welded anchors, and post-installed anchors. An appendix provides three example designs for column pedestal anchors, octagonal pedestal anchors, and shear lug pipe sections. Topics include an overview of design methods for tension and shear transfer with reinforcement and other embedments as used in the petrochemical industry; anchorage materials and properties; cast-in-place anchors; post-installed anchors; and recommended installation and repair. This report will be useful to petrochemical or structural engineers, as well as by managers of companies operating petrochemical facilities. It will also be useful for structural engineers in other industries who anchor structural steel and equipment to concrete foundations and structures. --